2015
DOI: 10.1186/s12910-015-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ reaction to the ethical conduct of radiographers and staff services as predictors of radiological experience satisfaction: a cross-sectional study

Abstract: BackgroundPatients’ satisfaction arises from their appraisal of experience in hospital services and measuring patients’ satisfaction in hospital has become a global phenomenon. To improve on patients’ satisfaction, radiographers have to imbibe the right ethical attitude in their conduct while discharging duties to patients during radiological examination. The objective of this study is to understand from the patients’ perspective the ethical conduct of radiographers and radiology nurses that constitute factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…The result is in line with studies conducted in Nigeria, 73.4% [14], Philippines, 71% [18] and Pakistan, 71.2% [19]. Moreover, the same or comparable proportion of satisfied patients in this study may not imply that the radiological service rendered in the radiology department is of high quality and good performance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The result is in line with studies conducted in Nigeria, 73.4% [14], Philippines, 71% [18] and Pakistan, 71.2% [19]. Moreover, the same or comparable proportion of satisfied patients in this study may not imply that the radiological service rendered in the radiology department is of high quality and good performance.…”
Section: Discussionsupporting
confidence: 88%
“…The hospital, which currently has 400 beds, went operational in 2003 and is affiliated to the Hawassa University, in which the service is delivered by organizing in to four major departments: medical, surgical, pediatric, and gynecology and obstetrics departments, and other clinics like TB-HIV care unit, ART(Anti-Retroviral Therapy) clinic, Volunteer counseling and testing (VCT), ophthalmology unit, surgical and medical emergency unit, radiology unit, Intensive Care Unit (ICU) unit and Anesthesiology unit. According to the hospital annual and monthly report, the hospital has about 400 up to 500 daily outpatient visits on average [14], including approximately 70 daily radiology visits. The radiology department gives services in three main categories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that 75% of the patients were satisfied with the radiological service they received. The result is in line with the studies conducted in Nigeria, 73.4% [12], Southern Ethiopia, 71.6% [13], Philippines, 71% [14], and Pakistan [15], 71.2% [16].…”
Section: Discussionsupporting
confidence: 79%
“…Patients' satisfaction was measured using a patients' satisfaction structured questionnaire developed by researchers based on the previous search [11,12]. It was measured by asking questions about different domains on a scale of excellent to poor.…”
Section: Methodsmentioning
confidence: 99%